Polymer material, emulsion, adhesive, negative pole piece, secondary battery and electric device

By using polymer material with core-shell structure as adhesive in secondary batteries, the problem of cracking of the negative electrode sheet is solved, the flexibility and adhesion of the electrode sheet is improved, the service life of the battery is extended and the performance is improved.

CN119708509AActive Publication Date: 2025-03-28CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311277205.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

The cracking problem of the negative electrode plate in the secondary battery leads to a degradation of battery performance and shortening of service life.

Method used

A polymer material with a core-shell structure is used as the adhesive to improve the flexibility of the electrode sheet by uniformly applying it on the electrode sheet and reduce local stress accumulation.

Benefits of technology

It effectively alleviates the problem of cracking of the electrode sheet, improves the flexibility and adhesion of the electrode sheet, extends the service life of the battery and improves performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708509A_ABST
    Figure CN119708509A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a polymer material, an emulsion, an adhesive, a negative pole piece, a secondary battery and an electric device. The polymer material comprises a polymer unit, the polymer unit has a core-shell structure, the core-shell structure comprises a core part and a shell part, the shell part at least partially covers the core part, the core part comprises a sulfonic acid styrene-acrylic copolymer, and the shell part comprises sulfonic acid type polyurethane. The sulfonic acid type polyurethane serving as the shell part is anionic waterborne polyurethane, the hydrophilic center of the sulfonic acid type polyurethane is mainly sulfonate radical, and the dispersity of the core-shell structure polymer is improved. The core part is a styrene-acrylic copolymer containing a hydrophilic group, and the core part and the shell part are subjected to ionic bonding and / or covalent bonding to form a stably dispersed core-shell structure polymer unit. The stably dispersed core-shell structure polymer unit is used for forming a pole piece binder, so that the adhesion between the pole piece binder and an active material can be improved, the flexibility of the pole piece can be improved, and the problem of cracking of the pole piece can be relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a polymer material, an emulsion, an adhesive, a negative electrode sheet, a secondary battery and an electrical device. Background Art

[0002] Secondary batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features such as light weight, no pollution, and no memory effect. Among them, lithium-ion batteries are widely used in portable electronic devices, electric vehicles and other fields.

[0003] As the application scope of secondary batteries becomes wider and wider, the requirements for battery performance are getting higher and higher, the energy density of secondary batteries is also getting higher and higher, and the problem of electrode cracking is becoming increasingly prominent. Summary of the invention

[0004] In view of the above problems, the present application provides a polymer material, an emulsion, an adhesive, a negative electrode plate, a secondary battery and an electrical device, which are helpful to alleviate the problem of cracking of the electrode plate.

[0005] The first aspect of the present application provides a polymer material, comprising a polymer unit, wherein the polymer unit has a core-shell structure, and the core-shell structure comprises:

[0006] Core: contains sulfonic acid styrene acrylic copolymer;

[0007] Shell: comprising sulfonic acid type polyurethane;

[0008] The shell portion at least partially covers the core portion, and a mass ratio of the core portion to the shell portion is 1:(1-2).

[0009] In the present application, the sulfonic acid polyurethane as the shell part is an anionic waterborne polyurethane, and its hydrophilic center is mainly sulfonate, which is beneficial to improve the dispersibility of the core-shell structure polymer. The core part is a styrene-acrylic copolymer containing a hydrophilic group, and the core part and the shell part are ionically bonded and / or covalently bonded to form a stably dispersed core-shell structure polymer unit. The stably dispersed core-shell structure polymer unit is used to prepare a binder for forming a pole piece, which can not only improve its adhesion to the active material, but also improve the flexibility of the pole piece, which is beneficial to alleviate the problem of cracking of the pole piece.

[0010] In some embodiments of the present application, the mass ratio of the core portion to the shell portion is 1:(1.1-1.8).

[0011] In some embodiments of the present application, based on the total mass of the polymer unit, the mass percentage content of the core portion is 40% to 47%, and the mass percentage content of the shell portion is 53% to 60%.

[0012] In some embodiments of the present application, the sulfonic acid styrene-acrylic copolymer comprises acrylamide monomers containing sulfonic acid groups, vinylbenzene monomers, acrylates and / or acrylic acid monomers reacted in a molar ratio of (0.2-1): (3-10): (88-97);

[0013] Preferably, the molar ratio of the acrylamide monomer containing sulfonic acid group, the vinylbenzene monomer to the acrylate and / or acrylic acid monomer is (0.5-1):(4-8):(90-95).

[0014] In some embodiments of the present application, the acrylamide monomer containing a sulfonic acid group comprises one or a combination of two or more of 2-acrylamide-2-methylpropanesulfonic acid, 2-acrylamidepropanesulfonic acid, 2-acrylamideethanesulfonic acid, 2-acrylamidedodecanesulfonic acid, and 2-(3-phenyl-acrylamide)-ethanesulfonic acid;

[0015] Preferably, the vinylbenzene monomer comprises one or a combination of styrene and methylstyrene;

[0016] Preferably, the acrylic acid ester monomer comprises one or a combination of two or more of ethyl acrylate, butyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, benzyl acrylate, methyl methacrylate, butyl methacrylate, phenyl methacrylate, and trimethacrylate;

[0017] Preferably, the acrylic monomer comprises acrylic acid, methacrylic acid or a combination of both.

[0018] In some embodiments of the present application, the sulfonic acid styrene-acrylic copolymer includes acrylamide monomers containing sulfonic acid groups, vinylbenzene monomers, acrylate monomers, and acrylic acid monomers reacted in a molar ratio of (0.7-1): (5-6): (70-75): (20-22).

[0019] In some embodiments of the present application, the sulfonic acid styrene-acrylic copolymer includes 2-acrylamide-2-methylpropane sulfonic acid, styrene, butyl acrylate, methyl methacrylate and acrylic acid in a molar ratio of 0.74:5.86:41.7:30.51:21.19.

[0020] In some embodiments of the present application, the weight average molecular weight of the sulfonic acid styrene-acrylic copolymer is 1600-2000.

[0021] In some embodiments of the present application, the weight average molecular weight of the sulfonic acid type polyurethane is 330,000 to 550,000.

[0022] In some embodiments of the present application, the sulfonic acid polyurethane comprises the following components in percentage by mass:

[0023] 1) Sulfonic acid type polyester diol, 50% to 60%;

[0024] 2) diisocyanate, 15% to 25%;

[0025] 3) Polyol small molecule chain extender, 5% to 13%;

[0026] 4) Hydrophilic chain extender, 8% to 20%;

[0027] 5) Capping agent, 1% to 5%.

[0028] In some embodiments of the present application, the sulfonic acid polyester diol is prepared by reacting sodium dimethyl sulfonate isophthalate, neopentyl glycol and adipic acid;

[0029] Preferably, the diisocyanate includes one or a combination of two or more of isophorone diisocyanate, hexamethylene diisocyanate, and toluene diisocyanate;

[0030] Preferably, the polyol small molecule chain extender includes one or a combination of two or more of pentanediol, 1,4-butanediol, 1,6-hexanediol, and trimethylolpropane;

[0031] Preferably, the hydrophilic chain extender includes one or a combination of two or more of sodium ethylenediamine ethanesulfonate, sodium 1,2-dihydroxy-3-propanesulfonate, and sodium hexamethylenediamine monopropanesulfonate;

[0032] Preferably, the capping agent comprises hydroxyethyl acrylate.

[0033] The second aspect of the present application is to provide an emulsion comprising the polymer material described in the first aspect and a solvent.

[0034] In some embodiments of the present application, the solid content of the emulsion is 40% to 50%, and the particle size is 100nm to 200nm.

[0035] In some embodiments of the present application, the solvent comprises water, preferably deionized water.

[0036] The third aspect of the present application is to provide a binder comprising a linear polymer and the emulsion described in the second aspect.

[0037] In some embodiments of the present application, the mass ratio between the linear polymer and the polymer in the emulsion is 1:(6-15), preferably 1:(8-12).

[0038] In some embodiments of the present application, the linear polymer comprises polyethylene oxide.

[0039] In some embodiments of the present application, the solid content of the binder is 30% to 60%, preferably 40% to 55%.

[0040] The fourth aspect of the present application is to provide a negative electrode plate, which comprises a negative electrode current collector and a negative electrode film arranged on at least one surface of the negative electrode current collector, and the negative electrode film comprises the adhesive described in the third aspect.

[0041] In some embodiments of the present application, based on the total weight of the negative electrode film, the mass percentage of the binder is 1.2% to 2.2%.

[0042] The fifth aspect of the present application is to provide a secondary battery comprising the negative electrode plate described in the fourth aspect.

[0043] The sixth aspect of the present application is to provide an electrical device comprising the polymer described in the first aspect, the emulsion described in the second aspect, the binder described in the third aspect, the negative electrode plate described in the fourth aspect, or the secondary battery described in the fifth aspect.

[0044] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0046] Figure 1 Schematic diagram of the polymer structure of some embodiments of the present application;

[0047] Figure 2 This is a schematic diagram of the adhesive structure of some embodiments of the present application;

[0048] Figure 3 Schematic diagram of the molecular structure of the adhesive in some embodiments of the present application;

[0049] Figure 4 A schematic diagram of the interaction relationship between adhesive molecules and active materials of the electrode in some embodiments of the present application;

[0050] Figure 5 A schematic diagram of the interaction relationship between adhesive molecules and lithium ions in some embodiments of the present application;

[0051] Figure 6A schematic diagram of the structure of a vehicle according to some embodiments of the present application;

[0052] Figure 7 A schematic diagram of the exploded structure of a battery according to some embodiments of the present application;

[0053] Figure 8 This is a tensile test diagram of the adhesive film of some embodiments of the present application;

[0054] Fig. 9 This is a test diagram of the elastic modulus of the adhesive film of some embodiments of the present application;

[0055] Fig.10 This is a test diagram of the elongation at break of the adhesive film of some embodiments of the present application;

[0056] The reference numerals in the specific implementation manner are as follows:

[0057] 10000, vehicles;

[0058] 1000, battery; 2000, controller; 3000, motor;

[0059] 100. Single cell;

[0060] 200, box body; 210, first part; 220, second part. DETAILED DESCRIPTION

[0061] Below, the polymer material, emulsion, binder, negative electrode plate, secondary battery and electric device of the present application are described in detail with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0062] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0063] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0064] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0065] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0066] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0067] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0068] As the application scope of secondary batteries becomes wider and wider, the requirements for battery performance are getting higher and higher, and the energy density of secondary batteries is also getting higher and higher. In previous studies, improving the energy density of batteries mainly focused on developing new main materials and increasing the operating voltage of batteries. In addition, the load can be increased by thick coating. Studies have shown that the microstructure and internal stress inside the coating are the main reasons for the change in the elastic modulus of the coating when the coating thickness is different. When preparing the coating, the thicker the coating, the higher the density, and the greater the internal stress, the greater the elastic modulus of the coating, and the uneven release of stress accumulation can easily lead to cracking of the pole piece.

[0069] Adhesives are mainly used to bond active substances. Conventional PVDF is limited in its ability to improve the flexibility of the pole piece due to its own structural limitations. CMC, SBR, etc. are flexible materials, but due to their own dispersion requirements, the production time of pole pieces is generally longer. In order to improve production efficiency, it is usually necessary to increase the baking temperature after coating to speed up production. However, this undoubtedly increases the probability of cracking of the pole piece.

[0070] In the past, in order to solve the cracking problem of negative electrode plates, plasticizers were usually added during the pulping process to increase the flexibility of the plates. However, this method still has the following problems:

[0071] 1. Additional delivery pipelines are required to transport plasticizers; 2. The amount of plasticizer added is difficult to control. If too much is added, the electrical performance will deteriorate; 3. During high-speed and thick coating, some plasticizers are highly hydrophilic, and the residual amount in the electrode is high and the dryness of the electrode cannot be guaranteed.

[0072] If the flexibility of the adhesive itself can be improved and compounded with the negative electrode active material in a friendly manner, it may be helpful to alleviate the problem of electrode cracking caused by local stress accumulation during the electrode drying process on the basis of improving the adhesion.

[0073] Based on the above considerations, in order to solve the cracking problem of the negative electrode plate in the secondary battery, the applicant obtained a polymer material, emulsion, adhesive, negative electrode plate, secondary battery and power-consuming device according to the above design concept and related experimental research.

[0074] First, the present application discloses a polymer material, the polymer material comprises a polymer unit, the polymer unit has a core-shell structure, the core-shell structure comprises a core and a shell, wherein the shell at least partially covers the core, the core comprises a sulfonic acid styrene-acrylic copolymer, the shell comprises a sulfonic acid type polyurethane, and specifically, the sulfonic acid type polyurethane as the shell is an anionic waterborne polyurethane, and its hydrophilic center is mainly a sulfonate group, which is conducive to improving the dispersibility of the core-shell structure polymer. The conventional core does not include a hydrophilic group, and the present application adopts a styrene-acrylic copolymer comprising a sulfonate group (hydrophilic group), and further controls the mass ratio of the core to the shell to be 1: (1-2), so as to facilitate the core and the shell to form a stable and dispersed core-shell structure polymer unit in a manner such as ionic bonding and / or covalent bonding. The stable and dispersed core-shell structure polymer unit not only has good storage stability, but also has good flexibility and excellent bonding agent with active materials. In addition, the core-shell structure polymer unit applied to the pole piece can be evenly coated on the pole piece and improve the flexibility of the pole piece, which is helpful to alleviate the technical problem of pole piece cracking.

[0075] The polymer material disclosed in the embodiment of the present application is used to form a negative electrode adhesive and is applied to a negative electrode plate. The polymer is not suitable for a positive electrode plate, probably because the excessively high potential of the positive electrode will affect the structural stability of the polymer. The negative electrode plate containing the polymer can be formed into a secondary battery with a positive electrode plate, a separator, an electrolyte, etc. using any conventional process in the art. The secondary battery can be applied to, but not limited to, electrical devices such as vehicles, ships, or aircraft; further, the electrical device is applied to a power system, which is conducive to improving the storage performance and cycle performance of the power system.

[0076] The embodiment of the present application provides an electric device using a secondary battery as a power source. The electric device may include, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, and the like. Among them, the electric toy may include a fixed or mobile electric toy, for example, a game console, an electric car toy, an electric ship toy, and an electric airplane toy, and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, and the like.

[0077] polymer

[0078] like Figure 1 As shown, the present application discloses a polymer material in some embodiments, which includes a polymer unit, and the polymer unit has a core-shell structure. The core-shell structure includes a core part and a shell part, the core part includes a sulfonic acid styrene-acrylic copolymer, and the shell part includes a sulfonic acid polyurethane, wherein the mass ratio of the core part to the shell part is 1:(1~2).

[0079] The shell portion in the present application is located outside the core portion and the shell portion at least partially covers the core portion. In some embodiments of the present application, the shell portion completely covers the core portion. At the same time, the sulfonic acid polyurethane used as the shell portion in the present application is an anionic waterborne polyurethane, and its hydrophilic center is mainly a sulfonate group, which is beneficial to improve the dispersibility of the core-shell structure polymer. The styrene-acrylic copolymer of the present application is a styrene-acrylic copolymer containing a sulfonate group, and the mass ratio of the core portion to the shell portion is further controlled to be 1: (1 to 2), so that the core portion and the shell portion form a stably dispersed core-shell structure polymer unit by ionic bonding and / or covalent bonding. The stably dispersed core-shell structure polymer unit not only has good storage stability, but also has good flexibility and excellent adhesiveness with the active material. In addition, the core-shell structure polymer unit is applied to the pole piece to be evenly coated on the pole piece and improve the flexibility of the pole piece, which is beneficial to alleviate the technical problem of pole piece cracking.

[0080] In some embodiments of the present application, the mass ratio of the core to the shell is 1:(1.1-1.8).

[0081] The present application controls the mass ratio of the core to the shell to be 1:(1.1-1.8), which is conducive to forming a stably dispersed core-shell structure polymer unit.

[0082] In some embodiments of the present application, the mass ratio of the core to the shell may be one of 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2.0 or any one satisfying the range of values.

[0083] In some embodiments of the present application, based on the total mass of the polymer unit, the mass percentage content of the core portion is 40% to 47%, and the mass percentage content of the shell portion is 53% to 60%.

[0084] In the present application, the core and the shell constitute a polymer unit, and the mass percentage content of the core is controlled to be 40% to 47%, and the mass percentage content of the shell is controlled to be 53% to 60%, so that the shell completely covers the core and forms a stable, dispersed, and flexible core-shell structure polymer unit.

[0085] In some embodiments of the present application, the sulfonic acid styrene-acrylic copolymer includes acrylamide monomers containing sulfonic acid groups, vinylbenzene monomers, acrylates and / or acrylic acid monomers reacted in a molar ratio of (0.2-1): (3-10): (88-97).

[0086] The "and / or" in this application includes any one or two of acrylate monomers and acrylic acid monomers. Acrylate monomers have good water resistance, weather resistance and physical and mechanical properties, which can make up for the poor water resistance of sulfonic acid polyurethane and improve the flexibility of core-shell structure polymer units. Among them, poor water resistance includes the ability of polymers to resist water damage. Vinylbenzene monomers have alkenyl groups on the benzene ring, which also have good water resistance, while acrylic acid monomers and acrylamide monomers containing sulfonic acid groups are functional monomers. The functional monomers have functional groups of carboxyl, sulfonic acid and amide bonds, which are conducive to ionic bonding with the shell to form a stable and dispersed core-shell polymer.

[0087] The acrylamide monomer containing sulfonic acid group, vinylbenzene monomer, acrylate and / or acrylic acid monomer of the present application are reacted in a molar ratio of (0.2-1):(3-10):(88-97) to form a sulfonic acid styrene-acrylic copolymer comprising the following structural formula X.

[0088] A, B, and C in the structural formula X of the present application are selected from any one of acrylamide monomers containing sulfonic acid groups, vinylbenzene monomers, acrylates, and / or acrylic acid monomers, and a, b, and c include any positive integers.

[0089]

[0090] In some embodiments of the present application, the molar ratio of the acrylamide monomer containing a sulfonic acid group, the vinylbenzene monomer and the acrylate and / or acrylic acid monomer is (0.5-1):(4-8):(90-95).

[0091] The present application selects and controls the molar ratio of acrylamide monomers containing sulfonic acid groups, vinylbenzene monomers and acrylate and / or acrylic acid monomers to be (0.5-1):(4-8):(90-95), which is conducive to forming a water-resistant copolymer with certain flexibility and capable of cross-linking and / or ion bonding with sulfonic acid type polyurethane.

[0092] In some embodiments of the present application, the acrylamide monomer containing a sulfonic acid group includes but is not limited to one or a combination of two or more of 2-acrylamide-2-methylpropanesulfonic acid, 2-acrylamidepropanesulfonic acid, 2-acrylamideethanesulfonic acid, 2-acrylamidododecanesulfonic acid, and 2-(3-phenyl-acrylamide)-ethanesulfonic acid.

[0093] The acrylamide monomer containing sulfonic acid groups listed in the present application is a multifunctional water-soluble anionic surfactant monomer, which is convenient to copolymerize with other water-insoluble monomers to improve the water resistance of sulfonic acid styrene-acrylic copolymers and introduce groups capable of ion bonding with sulfonic acid polyurethanes.

[0094] In some embodiments of the present application, the vinylbenzene monomer includes but is not limited to one or a combination of two or more of styrene and methyl styrene, wherein the methyl styrene includes ortho-, meta- and para-substituted methyl styrene.

[0095] The vinylbenzene monomers listed in the present application are convenient for introduction into the cross-linking groups for forming the sulfonic acid styrene-acrylate copolymers through cross-linking, and are also beneficial for improving the water resistance of the sulfonic acid styrene-acrylate copolymers.

[0096] In some embodiments of the present application, the acrylate monomer includes but is not limited to one or a combination of two or more of ethyl acrylate, butyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, benzyl acrylate, methyl methacrylate, butyl methacrylate, phenyl methacrylate, and trimethacrylate.

[0097] The acrylic acid ester monomers listed in this application are beneficial to improving the flexibility and water resistance of the sulfonic acid styrene acrylic copolymer.

[0098] In some embodiments of the present application, the acrylic monomer includes but is not limited to one or a combination of two or more of acrylic acid and methacrylic acid.

[0099] The acrylic monomer provided in the present application is convenient for introducing a group capable of ion bonding with the sulfonic acid type polyurethane to improve the stability of the core-shell structure polymer.

[0100] In some embodiments of the present application, the sulfonic acid styrene-acrylic copolymer includes acrylamide monomers containing sulfonic acid groups, vinylbenzene monomers, acrylate monomers, and acrylic acid monomers reacted in a molar ratio of (0.7-1): (5-6): (70-75): (20-22).

[0101] In some embodiments of the present application, the sulfonic acid styrene-acrylic copolymer includes 2-acrylamide-2-methylpropanesulfonic acid, styrene, butyl acrylate, methyl methacrylate and acrylic acid in a molar ratio of 0.74:5.86:41.7:30.51:21.19.

[0102] As shown in the following general formula I, the present application provides a structural formula of a sulfonic acid styrene-acrylic copolymer, wherein x1, x2, x3, x4 and x5 in the structural formula include any positive integers conventional in the art, and R in the structural formula I 1 , R 1 Selected from alkyl groups.

[0103] The present invention is conducive to forming a sulfonic acid styrene-acrylic copolymer having water resistance and flexibility by selecting a reasonable amount of each monomer.

[0104]

[0105] In some embodiments of the present application, the weight average molecular weight of the sulfonic acid styrene-acrylic copolymer is 1600-2000.

[0106] The weight average molecular weight in this application includes any meaning in the art, wherein the weight average molecular weight can be obtained by calculation, or can be directly measured by experimental techniques such as gel permeation chromatography (GPC) or physical methods such as light scattering. At this weight average molecular weight, it is beneficial to improve the water resistance and flexibility of the sulfonic acid styrene-propylene copolymer.

[0107] In some embodiments of the present application, a 200-GPC gel permeation chromatograph produced by PE Company of the United States is used to determine the weight average molecular weight of the sulfonic acid styrene-acrylic copolymer. Specifically, a polystyrene standard sample is used and tetrahydrofuran is used as a solvent.

[0108] In some embodiments of the present application, the weight average molecular weight of the sulfonic acid polyurethane is 330,000 to 550,000.

[0109] The weight average molecular weight of the sulfonic acid polyurethane of the present application is 330,000 to 550,000, which is much larger than the sulfonic acid styrene acrylic copolymer. The sulfonic acid polyurethane is coated on the outside of the sulfonic acid styrene acrylic copolymer to form a stable dispersed core-shell structure polymer.

[0110] In some embodiments of the present application, a 200-GPC gel permeation chromatograph produced by PE Company of the United States is used to determine the weight average molecular weight of the sulfonic acid type polyurethane. Specifically, a polystyrene standard sample is used and tetrahydrofuran is used as a solvent.

[0111] In some embodiments of the present application, the sulfonic acid polyurethane is prepared by including the following components in percentage by weight:

[0112] 1) Sulfonic acid type polyester diol, 50% to 60%;

[0113] 2) diisocyanate, 15% to 25%;

[0114] 3) Polyol small molecule chain extender, 5% to 13%;

[0115] 4) Hydrophilic chain extender, 8% to 20%;

[0116] 5) Capping agent, 1% to 5%.

[0117] The sulfonic acid polyester diol in this application mainly constitutes the flexible soft segment of the sulfonic acid polyurethane, while the diisocyanate and the polyol small molecule chain extender mainly constitute the hard segment of the sulfonic acid polyurethane. Among them, the hard segment and the soft segment include the conventional definitions in the art, for example, the glass transition temperature is lower than room temperature for the soft segment, and higher than room temperature for the hard segment. This application forms a sulfonic acid polyurethane with appropriate flexibility and hardness through the reasonable combination of soft segment and hard segment. At the same time, the sulfonic acid group is introduced into the flexible soft segment to further improve the water solubility of the polyurethane and form a stably dispersed core-shell structure polymer.

[0118] The structural formula of the sulfonic acid type polyurethane of the present application is shown in the following formula II:

[0119]

[0120] In Formula II of the present application, R 1 With R 2 Any one selected from a capping agent and a hydrophilic chain extender, and x6 also includes any positive integer conventional in the art.

[0121] The present application selects the raw material components in the above ratio to prepare sulfonic acid polyurethane, which has suitable water solubility and is conducive to forming a stably dispersed core-shell structure polymer.

[0122] The sulfonic acid polyurethane of the present application can be well dispersed in a solvent, such as water, to form an emulsion, and these emulsions are stable dispersions and have a suitable particle size.

[0123] In some embodiments of the present application, the sulfonic acid polyester diol is prepared by reacting sodium dimethyl sulfonate isophthalate, neopentyl glycol and adipic acid.

[0124] The preparation route of the sulfonic acid type polyester diol of the present application can be as follows:

[0125]

[0126] In the above preparation route of this application, R 3 With R 4 Selected from alkyl groups, such as R 3 is neopentyl, R 4 For n-butane, etc.

[0127] The sulfonic acid polyester diol of the present application is convenient to be gradually polymerized with components such as diisocyanate and polyol small molecule chain extender to form a sulfonic acid polyurethane cross-linked at room temperature. In some embodiments of the present application, the end-capping agent is hydroxyethyl acrylate, the hydrophilic chain extender is sodium ethylenediamine sulfonate, and the specific sulfonic acid polyurethane is prepared by the following specific preparation route:

[0128]

[0129] In some embodiments of the present application, the diisocyanate includes but is not limited to one or a combination of two of isophorone diisocyanate, hexamethylene diisocyanate, and toluene diisocyanate.

[0130] In some embodiments of the present application, the diol small molecule chain extender includes, but is not limited to, one or a combination of two of pentanediol, 1,4-butanediol, 1,6-hexanediol, and trimethylolpropane.

[0131] In some embodiments of the present application, the hydrophilic chain extender includes, but is not limited to, one or a combination of two of sodium ethylenediamine ethanesulfonate, sodium 1,2-dihydroxy-3-propanesulfonate, and sodium hexamethylenediamine monopropanesulfonate.

[0132] In some embodiments of the present application, the capping agent includes but is not limited to hydroxyethyl acrylate.

[0133] In some embodiments of the present application, the reaction raw materials for preparing the sulfonic acid type polyurethane further include an organic tin compound, and the organic tin compound includes but is not limited to dibutyltin dilaurate.

[0134] In some embodiments of the present application, the preparation method of the polymer material is as follows:

[0135] The polymer material is prepared by adding acrylamide monomers, vinylbenzene monomers, acrylate and / or acrylic monomers containing sulfonic acid groups into the sulfonic acid type polyurethane and polymerizing them.

[0136] Lotion

[0137] According to some embodiments of the present application, the present application provides an emulsion.

[0138] In some embodiments, the polymer unit having a core-shell structure is dispersed in a solvent, such as water, to form an emulsion. The emulsion is a stable dispersion and has a suitable particle size.

[0139] In some embodiments of the present application, the solid content of the emulsion is 40% to 50%, and the particle size is 100 nm to 200 nm.

[0140] When the solid content of the emulsion of the present application is 40% to 50%, the particle size of the formed emulsion is 100nm to 200nm. The emulsion of the present application contains a strongly acidic hydrophilic group, and the ionization strength in the emulsion is increased, which promotes the formation of a strong electrostatic repulsion between the colloid particles in the emulsion, and can effectively prevent the aggregation between the colloid particles to form a stable dispersed emulsion.

[0141] In some embodiments of the present application, the particle size of the emulsion is 140 nm to 150 nm.

[0142] The particle size distribution of the emulsion prepared in the present application is relatively uniform.

[0143] The solid content in this application includes any conventional meaning in the art, which includes the ratio of the mass of solid matter in the emulsion to the total mass. The test method of solid content includes any conventional form in the art, such as drying method, combustion method, etc. This application chooses to use the drying method to measure the specific value of solid content. For example, a certain amount of sample (W1) is dried at a certain temperature for 3 hours, cooled to room temperature and weighed (W2), then the solid content of the emulsion = W2 / W1.

[0144] The particle size distribution of the emulsion of the present application can be directly measured by a particle size analyzer. For example, a certain amount of the emulsion is placed in a beaker, and after standing for a few minutes, it is visually inspected whether there is precipitation at the bottom of the beaker, and then the emulsion is picked up with a glass rod to observe whether there is evenly dispersed liquid on the glass rod. Finally, a small amount of sample is taken and diluted, and the particle size analyzer produced by Zhuhai OMEC Instrument Co., Ltd. is used to determine the emulsion particle size and its distribution.

[0145] In some embodiments of the present application, the solvent is deionized water.

[0146] Adhesive

[0147] According to some embodiments of the present application, the present application provides an adhesive, which comprises a linear polymer and the above-mentioned emulsion. Figure 2 As shown in the figure, the latex of the core-shell polymer is compounded with the linear polymer to form a uniformly dispersed adhesive. In the adhesive, the linear polymer is cross-distributed to form a network structure, and the polymer with the core-shell structure is uniformly dispersed inside and outside the network structure. Therefore, the adhesive is conducive to improving its adhesion with the negative electrode active material and other components.

[0148] In some embodiments of the present application, the linear polymer contains groups capable of forming intermolecular hydrogen bonds, such as hydroxyl groups, ether groups, etc. Figure 3 It is shown that the sulfonic acid polyurethane in the core-shell structure polymer has certain flexibility and mobility. The functional groups it contains, such as sulfonic acid group, ester group, carboxylic acid group, amide bond, etc., are easy to form intermolecular hydrogen bonds with different energy gradients with hydroxyl group, ether oxygen group, etc. in linear polymers. With the help of the flexibility and mobility of the sulfonic acid polyurethane itself, it is convenient to accelerate the spatial twisting and reversibility of intermolecular hydrogen bonds with different energy gradients, which is beneficial to quickly release stress and reduce the probability of electrode cracking. In particular, it can improve the local stress accumulation during the electrode baking process.

[0149] In some embodiments of the present application, the binder can form intermolecular hydrogen bonds with the negative electrode active material, such as the negative electrode active material having oxygen-containing functional groups on the surface, to reduce the generation of stress. Figure 4It is shown that the adhesive has good bonding force with the negative electrode active material (graphite), and this bonding force is conducive to improving the flexibility of the electrode and thus reducing the probability of cracking of the electrode. Figure 5 In the description, only graphite is used as one of the representatives of negative electrode active materials. The negative electrode active materials of the present application also include other materials having oxygen-containing functional groups on the surface.

[0150] Combination Figure 5 It can be seen that the adhesive can also improve the mobility of lithium ions in the negative electrode active material. Specifically, the functional groups in the adhesive, such as sulfonic acid groups, amide bonds, etc., easily adsorb lithium ions and promote the migration of lithium ions in the negative electrode active material. For example, lithium ions are coupled with ether oxygen bonds on polymer segments, and the binder segments keep moving in situ to generate free volume, so that lithium ions can migrate from coordination site to coordination site and jump from segment to segment along the polymer segments. On the one hand, after being adsorbed, lithium ions promote the decomposition of lithium electrolyte salts, such as lithium hexafluorophosphate, accelerate the desolvation process of lithium ions and induce the construction of LiF-rich SEI. On the other hand, the conduction rate of lithium ions in the SEI film is also accelerated, and ultimately the kinetic performance of the secondary battery is improved.

[0151] In some embodiments of the present application, the mass ratio between the linear polymer and the polymer in the emulsion is 1:(6-15).

[0152] The linear polymer in the present application is cross-linked in the binder to form a network structure, and the polymer in the emulsion is evenly dispersed inside and outside the network structure, which is beneficial to improving the flexibility of the adhesive.

[0153] In some embodiments of the present application, the mass ratio between the linear polymer and the polymer in the emulsion is 1:(8-12).

[0154] The present application selects to control the mass ratio between the linear polymer and the polymer in the emulsion to be 1:(8-12), which is beneficial to the connection between the linear polymer and the polymer in the emulsion and the formation of a stably dispersed adhesive.

[0155] In some embodiments of the present application, the linear polymer comprises polyethylene oxide.

[0156] The polyethylene oxide of the present application has a linear structure, and the linear structure contains functional groups, which are conducive to forming intermolecular hydrogen bonds with the polymer in the emulsion.

[0157] In some embodiments of the present application, the solid content of the binder is 30% to 60%, preferably 40% to 55%.

[0158] The solid content of the binder of the present application is also measured by the drying method. For example, a certain amount of sample (W1) is dried at a certain temperature for 3 hours, cooled to room temperature and weighed (W2), then the solid content of the emulsion = W2 / W1.

[0159] Negative electrode

[0160] The binder disclosed in the embodiment of the present application can be mixed with negative electrode active materials, conductive agents, dispersants, etc. to form negative electrode slurry, and the negative electrode slurry is formed on at least one surface of the negative electrode collector to form a negative electrode film, and the negative electrode film is dried to obtain a negative electrode sheet.

[0161] In the present application, the method of forming the negative electrode slurry on the surface of the negative electrode current collector includes any conventional form in the art, such as coating, etc. At the same time, the drying process of the present application also includes any conventional form in the art.

[0162] The adhesive provided in the present application is convenient for forming intermolecular hydrogen bonds with more contact sites with negative electrode active materials, such as graphite with oxygen-containing functional groups on the surface, so as to reduce the generation of stress, which is beneficial to improve the flexibility of the electrode and thus reduce the probability of cracking of the electrode.

[0163] According to some embodiments of the present application, based on the total weight of the negative electrode film, the mass percentage content of the binder is 1.2% to 2.2%.

[0164] According to some embodiments of the present application, based on the total mass of the negative electrode film, the mass percentage content of the conductive agent is 0.2% to 2.0%.

[0165] According to some embodiments of the present application, based on the total mass of the negative electrode membrane, the mass percentage content of the dispersant is 0.2% to 2.0%.

[0166] The conductive agent in the present application includes any conventional type in the art, such as one or a combination of two or more of graphite, superconducting carbon, carbon black (such as acetylene black, Ketjen black, Super P, etc.), carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0167] The dispersant in the present application also includes any conventional type in the art, such as cellulose and its salts, specifically including but not limited to methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose and the like.

[0168] The negative electrode active material in the present application includes a carbonaceous material, and the carbonaceous material includes one or a combination of two or more of artificial graphite, natural graphite, soft carbon, and hard carbon. Among them, artificial graphite, natural graphite, soft carbon, hard carbon, etc. include materials of any form conventional in the art, and include any conventional manufacturers and models in the art. At the same time, the negative electrode active material may also include a silicon-based material, and the silicon-based material includes one or two of a silicon-oxygen material or a silicon-carbon material. In addition, the negative electrode active material may also include a silicon-carbon composite, a Li-Sn alloy, a Li-Sn-O alloy, Sn, SnO, SnO 2 、TiO 2 -Li 4 Ti 5 O 12 , Li-Al alloy. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for lithium-ion batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.

[0169] The negative electrode current collector in the present application may be a metal foil or a composite current collector, the metal foil may be a copper foil, and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and the like.

[0170] Positive electrode

[0171] The positive electrode sheet in the present application includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material, a positive electrode conductive agent, a positive electrode binder, etc. The present application does not specifically limit the specific type of the positive electrode active material. For example, when the positive electrode sheet is used in a lithium-ion battery, the positive electrode active material includes but is not limited to LiCoO 2 、LiNiO 2 、LiMnO 2 、LiMn 2 O 4 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (NCM111) 、 LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523) 、LiNi 0.6 CO0.2 Mn 0.2 O 2 (NCM622) 、 LiNi 0.8 CO 0.1 Mn 0.1 O 2 (NCM811) 、LiNi 0.85 CO 0.15 Al 0.05 O 2 、LiFePO 4 (LFP) and LiMnPO 4 One or more of. The positive electrode conductive agent includes but is not limited to one or more combinations of graphite, superconducting carbon, carbon black (such as acetylene black, Ketjen black, Super P, etc.), carbon dots, carbon nanotubes, graphene and carbon nanofibers. The positive electrode binder includes but is not limited to polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorine-containing acrylate resin, styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid, carboxymethyl chitosan, etc. One or more combinations. The positive electrode current collector in the present application can be a metal foil or a composite current collector, wherein the metal foil can be an aluminum foil, and the composite current collector can include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector can be formed by forming metal materials such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0172] Electrolyte

[0173] The electrolyte in the present application is used to achieve ion conduction between the positive electrode plate and the negative electrode plate. The electrolyte includes an electrolyte salt and a solvent, wherein the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate. The solvent may include at least one selected from ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone or an ether solvent such as triethylene glycol dimethyl ether.

[0174] Isolation film

[0175] In the present application, the separator between the positive electrode and the negative electrode can be any known porous structure separator with good chemical stability and mechanical stability. For example, the material of the separator may include but is not limited to one or a combination of two or more of the following groups: glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film without special restrictions. When the separator is a multi-layer composite film, the materials of each layer can be the same or different without special restrictions.

[0176] Electrical devices

[0177] For the convenience of explanation, some embodiments of the present application are described by taking a vehicle as an example of an electrical device.

[0178] Please refer to Figure 6 , Figure 6 A schematic diagram of the structure of a vehicle 10000 provided for some embodiments of the present application. The vehicle 10000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 1000 is provided inside the vehicle 10000, and the battery 1000 may be provided at the bottom, head or tail of the vehicle 10000. The battery 1000 may be used to power the vehicle 10000, for example, the battery 1000 may be used as an operating power source for the vehicle 10000. The vehicle 10000 may also include a controller 2000 and a motor 3000, and the controller 2000 is used to control the battery 1000 to power the motor 3000, for example, for the starting, navigation and working power requirements of the vehicle 10000 during driving.

[0179] In some embodiments of the present application, the battery 1000 can not only serve as the operating power source of the vehicle 10000, but also serve as the driving power source of the vehicle 10000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 10000.

[0180] Please refer to Figure 6 , Figure 7 The exploded diagram of the battery 1000 provided in some embodiments of the present application. The battery 1000 includes a housing 200 and a single cell 100. Conventional single cells include primary cells or secondary cells. The present application specifically protects secondary cells. The single cell 100 is contained in the housing 200. The housing 200 is used to provide a containing space for the single cell 100. The housing 200 can adopt a variety of structures.

[0181] In some embodiments, the box body 200 may include a first part 210 and a second part 220, the first part 210 and the second part 220 cover each other, and the first part 210 and the second part 220 jointly define a storage space for accommodating the secondary battery 100. The second part 220 may be a hollow structure with one end open, and the first part 210 may be a plate-like structure, and the first part 210 covers the open side of the second part 220, so that the first part 210 and the second part 220 jointly define a storage space; the first part 210 and the second part 220 may also be hollow structures with one side open, and the open side of the first part 210 covers the open side of the second part 220. Of course, the box body 200 formed by the first part 210 and the second part 220 may be in various shapes, such as a cylinder, a cuboid, etc.

[0182] In the battery 1000, there may be multiple single cells 100, and the multiple single cells 100 may be connected in series, in parallel, or in mixed connection. Mixed connection means that the multiple single cells 100 are both connected in series and in parallel. The multiple single cells 100 may be directly connected in series, in parallel, or in mixed connection, and then the whole formed by the multiple single cells 100 is accommodated in the box 200; of course, the battery 1000 may also be a battery 1000 module formed by connecting multiple single cells 100 in series, in parallel, or in mixed connection, and then the multiple battery 1000 modules are connected in series, in parallel, or in mixed connection to form a whole, and then accommodated in the box 200. The battery 1000 may also include other structures, for example, the battery 1000 may also include a busbar component for realizing electrical connection between the multiple single cells 100.

[0183] The single cell 100 may be a lithium-ion battery, a sodium-ion battery or other batteries, and the single cell 100 may be cylindrical, flat, rectangular or in other shapes.

[0184] [Preparation of emulsion]

[0185] 1. Preparation of polyester diol:

[0186] According to the mass parts, 40 parts of neopentyl glycol (NPG) and 18.6 parts of sodium 5-sulfoisophthalate (SIPM) were added into a four-mouth reactor. 2 Half an hour later, in N 2 The temperature was raised under protection at a rate of 2°C / min, and stirring began after all NPG was melted. The temperature was then raised to 200°C for ester exchange reaction for 3 hours, and the temperature was lowered to 85°C, 11.5 parts of adipic acid (HA) were added, and stirred for half an hour, 0.2 parts of diisobutyltin dilaurate were added, the temperature was raised to 150°C, and the temperature was kept constant for 1.5 hours for polycondensation, and then the temperature was raised to 210°C, and the reaction was carried out for 2 hours, and water was removed by rotary evaporation to obtain polyester diol.

[0187] 2. Preparation of sulfonic acid polyurethane emulsion:

[0188] Take 14 parts of the above polyester diol and add them to a three-mouth reactor, vacuum dehydrate at 100°C for 1h, cool to 40°C, add 5 parts of isophorone diisocyanate (IPDI), 1.25 parts of trimethylolpropane (TMP) and 0.12 parts of diisobutyltin dilaurate to prepolymerize. Stir slowly, then add 2 parts of pentanediol, 0.5 parts of end-capping agent hydroxyethyl acrylate (HEA), 2.2 parts of hydrophilic chain extender sodium ethylenediamine sulfonate (A95), react at 75-80°C for 0.5h, then adjust the speed to 1800r / min, add 60 parts of deionized water for shear emulsification and dispersion, and obtain sulfonic acid type polyurethane emulsion.

[0189] 3. Preparation of polymer emulsion:

[0190] Styrene, butyl acrylate, methyl methacrylate and acrylic acid were added to the above sulfonic acid polyurethane emulsion, and the molar ratio was controlled to be 0.74:5.86:41.7:30.51:21.19.

[0191] Then add a proper amount of initiator potassium persulfate (KPS), keep the temperature at 85°C, react for 3 hours, cool down by 40°C, filter, and adjust the pH to 6-7 with sodium bicarbonate to obtain an emulsion.

[0192] The raw materials and compositions for preparing sulfonic acid type polyurethane and sulfonic acid type styrene acrylic copolymer are shown in Table 1 and Table 2.

[0193] Table 1 List of sulfonic acid styrene acrylic copolymers

[0194]

[0195]

[0196]

[0197] The present application uses the weight average molecular weight (1600 to 1800) of the sulfonic acid styrene acrylic copolymer prepared in the above specific embodiment as an explanation, but the sulfonic acid styrene acrylic copolymer of the present application also includes other copolymers with a molecular weight between 1600 and 2000.

[0198] Table 2 List of sulfonic acid type polyurethanes

[0199]

[0200] The weight average molecular weight of the sulfonic acid polyurethane prepared in the above embodiment of the present application is about 400,000, and the present application only uses this specific value as an explanation. However, the sulfonic acid polyurethane of the present application also includes other polymers with a molecular weight between 330,000 and 550,000.

[0201] Table 3 Emulsion List

[0202]

[0203]

[0204] In conjunction with Table 3 of the present application, the emulsion particle size includes 140nm to 150nm which is uniformly distributed as a representative, but the emulsion particle size of the present application also includes other values ​​between 100nm and 200nm.

[0205] [Preparation of binder]

[0206] Add 10 parts of PEO (polyethylene oxide) with a weight average molecular weight (4 million to 6 million) to 50 parts of deionized water and stir for 5 hours to form a uniform solution;

[0207] The polymer emulsion and the PEO solution were mixed evenly at an actual solid content ratio of 10:1 to obtain a binder.

[0208] [Preparation of adhesive film and performance testing]

[0209] (1) Preparation of adhesive film: Weigh 10g of adhesive according to the solid content, add 100g of 2% CMC glue solution dispersed in advance, stir and disperse for 30 minutes at a speed of 600r / min. Then weigh 80g of the mixed sample and pour it into a 10cm×10cm mold, spread it evenly, and then put it into a vacuum drying oven, evacuate it at room temperature for 4 hours to remove bubbles. Then take it out and put it into a 60℃ forced air drying oven to stand for 6 hours, peel off the film, and prepare a dumbbell-shaped strip for use.

[0210] (2) Tensile test of adhesive film:

[0211] Equipment used: Zhongzhi Testing Tensile Testing Machine (model LXG2-LLCS-0009) for testing.

[0212] (2.1) Test principle: The experimental principle of the film tensile test is to apply a gradually increasing tensile load in the length direction of the standard film strip to cause it to deform until it breaks. The maximum tensile stress required for the strip to break is the tensile strength. The change in the tensile strength of the strip is expressed by the elongation at break. On the straight line segment before the yield point of the stress-strain curve, the elastic modulus of the film can be obtained by selecting appropriate stress and strain.

[0213] Tensile strength: σt = p / bd;

[0214] Where: σt—tensile strength of rubber strip, N / mm 2 ;

[0215] P—maximum tensile load when the rubber strip breaks, N;

[0216] b—strip width, mm; the strip width is the width of the parallel part of the dumbbell-shaped strip;

[0217] d—strip thickness, mm;

[0218] The elongation at break of the film is: εt = (I-I0) / I0;

[0219] Where: εt—elongation at break, %;

[0220] I0—original gauge length of rubber strip, mm;

[0221] I—the length of the marking line when the rubber strip breaks, mm;

[0222] The elastic modulus of the film is: e = σ / ε;

[0223] Where: e—elastic modulus of the rubber strip, MPa;

[0224] σ—tensile stress, N / mm 2 ;

[0225] ε—strain, mm.

[0226] (2.2) Test method:

[0227] Cut 5 rubber strips longitudinally and transversely as required. The shape of the rubber strip is dumbbell-shaped. The specific dimensions are 120mm in length, 25mm in width at both ends of the dumbbell, 10mm in width of the narrow parallel part of the sample, and 0.4mm in thickness.

[0228] The specific test method is as follows:

[0229] For each rubber strip, measure the thickness at three points within the marking line and take the arithmetic mean with an accuracy of 1 micron;

[0230] When clamping the rubber strip, the longitudinal axis of the rubber strip should coincide with the center line of the upper and lower clamps of the testing machine, and the tightness should be appropriate;

[0231] Stretch at a specified speed of 100 mm / min;

[0232] After the rubber strip breaks, read the load and the elongation between the marking lines. If the rubber strip breaks somewhere outside the marking lines, take a new rubber strip and repeat the test.

[0233] When measuring the elastic modulus, the load and deformation are recorded by a strain recorder to calculate the tensile strength, elongation at break and elastic modulus.

[0234] Test results such as Figure 8 , Fig. 9 , Fig.10 .

[0235] Table 4 List of adhesives

[0236]

[0237]

[0238] For an ideal adhesive, its tensile strength and elongation at break are generally required to be as large as possible, while the elastic modulus should be moderate. If the elastic modulus is too small, it will not be able to restrain the expansion of the active material of the electrode, which may easily lead to severe rebound of the electrode. If the elastic modulus is too large, the electrode may easily crack.

[0239] From Table 4, it can be seen that the tensile strength and elongation at break of the adhesives provided in Examples 1 to 3 are not ideal, and the adhesive provided in Example 4 not only has unsatisfactory tensile strength and elongation at break, but also has an excessively large elastic modulus, which can easily lead to cracking of the pole piece.

[0240] In the present application, the amount of polyethylene oxide added affects the elastic modulus of the adhesive. Generally speaking, the more polyethylene oxide is added, the smaller the elastic modulus is and the better the flexibility is.

[0241] [Preparation of negative electrode sheet]

[0242] 4. Preparation of negative electrode slurry:

[0243] 1. Powder dry mixing: Add the negative electrode active material graphite, the conductive agent conductive carbon, and the stabilizer sodium carboxymethyl cellulose in a mass ratio of 96.7%:0.6%:0.24% into a mixer for dry powder mixing and stirring for 15 minutes, wherein the stirring revolution is 25 rpm and the stirring rotation is 800 rpm to obtain a uniform dry powder mixture;

[0244] 2. Stirring 1: Add part of deionized water to the dry powder mixture obtained in step 1 and stir for 60 minutes, wherein the ratio of deionized water is 44% to 46% of the negative electrode active material, and stir at 15 rpm;

[0245] 3. Stirring 2: 0.96% of the stabilizer sodium carboxymethyl cellulose and deionized water are added to the mixture obtained in step 2 in sequence and stirred for 65 minutes, wherein the stirring revolution is 25 rpm and the stirring rotation is 1800 rpm, to obtain a high-viscosity slurry with a viscosity of 8000-20000 Pa·s and a solid content of 50%-60%;

[0246] 4. Stirring three: Add 1.5% by weight of a binder to the high-viscosity slurry obtained in step 3 and stir for 30 minutes, wherein the stirring revolution is 25 rpm and the stirring rotation is 1200 rpm to obtain a uniformly mixed negative electrode slurry;

[0247] 5. Viscosity adjustment: If the viscosity of the slurry obtained in step 4 is too high, a small amount of deionized water needs to be added to the slurry to adjust the viscosity. The deionized water is added in small amounts and multiple times, and stirred for 20 minutes, with a stirring speed of 10 rpm and a stirring speed of 900 rpm. Finally, a negative electrode slurry with a viscosity of 3000 to 15000 Pa·s is obtained.

[0248] 6. Vacuum degassing: Seal the mixer, turn on the vacuum degassing until the vacuum degree in the mixer reaches above -50 KPa, stir for 20 minutes, with the stirring revolution of 10 rpm and the stirring rotation of 0 rpm, and finally obtain the negative electrode slurry with a solid content of 40% to 60%, which is set aside.

[0249] 5. Preparation of negative electrode sheet:

[0250] The prepared negative electrode slurry was evenly coated on the negative electrode current collector copper foil at a coating speed of 50 m / min and a coating mass of 300 mg / 1540.25 mm 2 The temperature settings of the nine ovens are 100℃ / 100℃ / 95℃ / 85℃ / 85℃ / 80℃ / 80℃ / 80℃ / 60℃; a cold press is used to compact the negative electrode sheet to a certain density (1.6~1.7g / 1540.25mm 2 ), the cold pressing pressure was set to 30 tons, the cold pressing speed was 15 m / min, the mass of the powder scraped off from the surface of the cold pressing roller by the scraper was collected during the cold pressing process, and the cohesive force of the negative electrode sheet after cold pressing was tested.

[0251] [Performance test of negative electrode]

[0252] According to some embodiments of the present application, the adhesion and cohesion tests are performed on the negative electrode sheets, wherein the raw materials for the tests come from the negative electrode sheets scraped off from the surface of the cold pressing roller of the cold press by a scraper during the cold pressing process in step (v) of the preparation of the negative electrode sheets.

[0253] (3) The bonding strength test of the negative electrode sheet is carried out using the equipment: Zhongzhi Testing Tensile Tester (Model LXG2-LLCS-0009); the specific test process is as follows:

[0254] ① Use a blade to cut a negative electrode sample with a width of 30mm and a length of (90mm to 150mm), and stick the double-sided tape on the steel plate with a width of 20mm and a length of (90mm to 150mm).

[0255] ② Paste the negative electrode sample in step ① onto the double-sided tape, wherein the exposed outer side of the negative electrode sample is used as the test surface, and roll the test surface three times along the same direction with a roller with a width of 20 mm;

[0256] ③ Turn on the power of the tensile testing machine, fix the end of the steel plate without the negative electrode sheet with the lower clamp, ensure that the steel plate is placed vertically with the base, and the bottom of the steel plate is flush with the base, fold the negative electrode sheet pasted on the steel plate upwards, and fix it with the upper clamp.

[0257] ④ Start pre-tensioning, pre-tensioning about 5mm, then "clear" the "force" and "displacement" parameters. After the two parameters are reset to zero, click the start button to start the test, and then record the test results. Perform three sets of tests in parallel according to the above steps, calculate the average value N1, and the final bonding force = N1×50.

[0258] (4) Cohesion test of negative electrode sheet: The cohesion test of negative electrode sheet is carried out by using the equipment: Zhongzhi Testing Tensile Tester (Model LXG2-LLCS-0009); the specific test process is as follows:

[0259] ⑤ Use a blade to cut the negative electrode sample with a width of 30mm × length of (90mm~150mm), and stick the double-sided tape on the steel plate with a width of 20mm × length of (90mm~150mm).

[0260] ⑥ Paste the negative electrode sample in step ⑤ onto the double-sided tape, wherein the exposed outer side of the negative electrode sample is used as the test surface, and a low-viscosity green tape with a width of 20 mm and a length greater than the length of the negative electrode sample by 80 mm to 200 mm is evenly pasted on the test surface, and a roller with a width of 20 mm is used to roll along the same direction of the test surface three times;

[0261] ⑦ Turn on the power of the tensile testing machine, fix the end of the steel plate without the negative electrode with the lower clamp, ensure that the steel plate is placed vertically with the base, and the bottom of the steel plate is flush with the base, fold the low-viscosity green glue upwards, and fix it with the upper clamp.

[0262] ⑧ Start pre-tensioning, pre-tensioning about 5mm, then "clear" the "force" and "displacement" parameters. After the two parameters are reset to zero, click the start button to start the test, and then record the test results. Perform three sets of tests in parallel according to the above steps, calculate the average value N2, and the final bonding force = N2×50.

[0263] Table 5 Negative electrode list

[0264]

[0265]

[0266] Generally speaking, for an ideal adhesive, the greater its adhesion and cohesion to the active material or other components in the negative electrode sheet, the better. Combined with Table 5, it can be seen that the content and specific type of the adhesive affect the values ​​of the above two values.

[0267] At the same time, the present application verifies the use effect of the adhesive of the present application by thick coating and baking at high temperature, and the results show that it can improve the cracking of the pole piece.

[0268] [Preparation of positive electrode sheet]

[0269] The positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2 O 2 The conductive agent Super-P and the binder polyvinylidene fluoride are stirred and dispersed in N-methylpyrrolidone in a mass ratio of 96:2:2 to prepare a positive electrode slurry, which is coated on the positive electrode current collector aluminum foil and compacted by a cold press to obtain a positive electrode sheet.

[0270] [Preparation of electrolyte]

[0271] Lithium salt LiPF was added to a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) with a mass ratio of 35:65. 6 , mix evenly to obtain an electrolyte, wherein LiPF 6 The molar concentration is 1 mol / L.

[0272] [Select a barrier film]

[0273] A polyethylene porous membrane with a thickness of 12 μm was selected.

[0274] [Preparation of lithium-ion batteries]

[0275] According to some embodiments of the present application, the prepared negative electrode sheet, the isolation membrane and the positive electrode sheet are stacked in order, so that the isolation membrane is placed between the positive and negative electrode sheets to play an isolation role, and are wound to obtain a bare battery cell, which is then inserted into a battery casing, and a soft-pack lithium-ion battery is obtained through processes such as baking, liquid injection, standing, packaging, formation, and capacity division.

[0276] [Performance test of lithium-ion batteries]

[0277] (4) Battery DC pulse resistance (DCR) performance test:

[0278] The above soft-pack lithium-ion battery is charged and discharged for a certain period of time, with a discharge depth of 50% SOC, and then the DCR value is calculated, such as:

[0279] DCR discharge (I 1 , t 1 )=|V 1 -V 2 | / I 1 ;

[0280] in:

[0281] I 1 is the discharge current value. The DCR performance test of this application generally controls the current to be above 0.33C; I 2 is the discharge current value;

[0282] t 1 The discharge duration is generally 10s to 30s.

[0283] V 1 is the voltage value at which discharge starts, V 2 is the voltage value at which discharge ends.

[0284] (5) Battery cycle performance test:

[0285] The lithium-ion battery was charged and discharged at 1C at 25°C, 45°C, and 60°C, respectively, and the capacity retention rate of the lithium-ion battery after 500 cycles was recorded.

[0286] (6) Battery storage performance test:

[0287] The lithium-ion battery was fully charged at 1C, and then stored at storage temperatures of 25°C, 45°C, and 60°C for 120 days, and the capacity retention rate of the lithium-ion battery after 120 days of storage was recorded.

[0288] Table 6 Lithium-ion battery list

[0289]

[0290]

[0291] Comparative Example 1

[0292] Provided is an adhesive, which is obtained by mixing the sulfonic acid type polyurethane of Example 1 with polyethylene oxide in a ratio of 10:1.

[0293] Comparative Example 2

[0294] Provided is an adhesive, which is obtained by mixing the sulfonic acid styrene-acrylic copolymer of Example 1 with polyethylene oxide in a ratio of 10:1.

[0295] Comparative Example 3

[0296] Provided is an adhesive, which comprises a polymer, wherein a core monomer in the polymer comprises butyl acrylate, methyl methacrylate and acrylic acid in a molar ratio of 41.7:30.51:21.19.

[0297] Comparative Example 4

[0298] The adhesive is SBR used in the prior art.

[0299] Combined with Table 6, it can be seen that the adhesive provided in the present application is helpful to reduce resistance, thereby improving the dynamic performance of the battery. At the same time, since the probability of cracking of the electrode is reduced, the cycle stability and storage performance of the battery are also improved.

[0300] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A polymer material, characterized in that The invention comprises a polymer unit, wherein the polymer unit has a core-shell structure, and the core-shell structure comprises: Core: contains sulfonic acid styrene acrylic copolymer; Shell: comprising sulfonic acid type polyurethane; The shell portion at least partially covers the core portion, and a mass ratio of the core portion to the shell portion is 1:(1-2).

2. The polymer material according to claim 1, characterized in that The mass ratio of the core portion to the shell portion is 1:(1.1-1.8).

3. The polymer material according to any one of claims 1 to 2, characterized in that Based on the total mass of the polymer unit, the mass percentage content of the core portion is 40% to 47%, and the mass percentage content of the shell portion is 53% to 60%.

4. The polymer material according to claims 1 to 2, characterized in that: The sulfonic acid styrene-acrylic copolymer comprises acrylamide monomer containing a sulfonic acid group, vinylbenzene monomer, acrylate and / or acrylic acid monomer, which are obtained by reacting in a molar ratio of (0.2-1): (3-10): (88-97); Preferably, the molar ratio of the acrylamide monomer containing sulfonic acid group, the vinylbenzene monomer to the acrylate and / or acrylic acid monomer is (0.5-1):(4-8):(90-95).

5. The polymer material according to claim 4, characterized in that The acrylamide monomer containing a sulfonic acid group comprises one or a combination of two or more of 2-acrylamide-2-methylpropanesulfonic acid, 2-acrylamidepropanesulfonic acid, 2-acrylamideethanesulfonic acid, 2-acrylamidedodecanesulfonic acid, and 2-(3-phenyl-acrylamide)-ethanesulfonic acid; Preferably, the vinylbenzene monomer comprises one or a combination of styrene and methylstyrene; Preferably, the acrylic acid ester monomer comprises one or a combination of two or more of ethyl acrylate, butyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, benzyl acrylate, methyl methacrylate, butyl methacrylate, phenyl methacrylate, and trimethacrylate; Preferably, the acrylic monomer comprises acrylic acid, methacrylic acid or a combination of both.

6. The polymer material according to claim 1, 2 or 5, characterized in that: The sulfonic acid styrene-acrylic copolymer comprises acrylamide monomers containing sulfonic acid groups, vinylbenzene monomers, acrylate monomers, and acrylic acid monomers, which are obtained by reacting in a molar ratio of (0.7-1): (5-6): (70-75): (20-22).

7. The polymer material according to claim 6, characterized in that The sulfonic acid styrene-acrylic copolymer is obtained by reacting 2-acrylamide-2-methylpropanesulfonic acid, styrene, butyl acrylate, methyl methacrylate and acrylic acid in a molar ratio of 0.74:5.86:41.7:30.51:21.

19.

8. The polymer material according to claim 1 or 2 or 5 or 7, characterized in that: The weight average molecular weight of the sulfonic acid styrene-acrylic copolymer is 1600-2000.

9. The polymer material according to any one of claims 1 to 8, characterized in that The weight average molecular weight of the sulfonic acid type polyurethane is 330,000 to 550,000.

10. The polymer material according to any one of claims 1 to 8, characterized in that The sulfonic acid type polyurethane is prepared by comprising the following components in percentage by mass: 1) Sulfonic acid type polyester diol, 50% to 60%; 2) diisocyanate, 15% to 25%; 3) Polyol small molecule chain extender, 5% to 13%; 4) Hydrophilic chain extender, 8% to 20%; 5) Capping agent, 1% to 5%.

11. The polymer material according to claim 10, characterized in that The sulfonic acid polyester diol is prepared by the reaction of sodium dimethyl sulfonate isophthalate, neopentyl glycol and adipic acid; Preferably, the diisocyanate includes one or a combination of two or more of isophorone diisocyanate, hexamethylene diisocyanate, and toluene diisocyanate; Preferably, the polyol small molecule chain extender includes one or a combination of two or more of pentanediol, 1,4-butanediol, 1,6-hexanediol, and trimethylolpropane; Preferably, the hydrophilic chain extender includes one or a combination of two or more of sodium ethylenediamine ethanesulfonate, sodium 1,2-dihydroxy-3-propanesulfonate, and sodium hexamethylenediamine monopropanesulfonate; Preferably, the capping agent comprises hydroxyethyl acrylate.

12. An emulsion, characterized in that A polymer material according to any one of claims 1 to 11, further comprising a solvent.

13. The emulsion according to claim 12, characterized in that The solid content of the emulsion is 40% to 50%, and the particle size is 100nm to 200nm.

14. The emulsion according to any one of claims 12 to 13, characterized in that The solvent comprises water, preferably deionized water.

15. A binder, characterized in that: The invention comprises a linear polymer and further comprises the emulsion according to any one of claims 12 to 14.

16. The adhesive according to claim 15, characterized in that The mass ratio between the linear polymer and the polymer in the emulsion is 1:(6-15), preferably 1:(8-12).

17. The adhesive according to any one of claims 15 to 16, characterized in that The linear polymer comprises polyethylene oxide.

18. The adhesive according to any one of claims 15 to 16, characterized in that The solid content of the binder is 30% to 60%, preferably 40% to 55%.

19. A negative electrode plate, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode film disposed on at least one surface of the negative electrode current collector, and the negative electrode film comprises the adhesive according to any one of claims 15 to 18.

20. The negative electrode plate according to claim 19, characterized in that: Based on the total weight of the negative electrode film, the mass percentage of the binder is 1.2% to 2.2%.

21. A secondary battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to any one of claims 19 to 20.

22. An electrical device, characterized in that: A secondary battery comprising the polymer material according to any one of claims 1 to 11, the emulsion according to any one of claims 12 to 14, the binder according to any one of claims 15 to 18, the negative electrode sheet according to any one of claims 19 to 20, or the secondary battery according to claim 21.

Citation Information

Patent Citations

  • Method for preparing polyurethane / polyacrylate core-shell emulsion

    CN102675553A

  • Sulfonic acid-type hydroxyl acrylic resin aqueous dispersion and preparation method thereof

    CN112341566A

  • Negative electrode binder with core-shell structure as well as preparation method and application of negative electrode binder

    CN116169292A

  • Waterborne polyurethane emulsion, preparation method thereof and two-component polyurethane adhesive

    CN116640288A

  • Reflective photomask blank, and manufacturing method of reflective photomask

    KR1020230159292A